Associations of abdominal obesity-related dietary patterns with prediabetes and type 2 diabetes: exploring the mediating effects of body composition and altitude in Tibetan adults - Bin Zhang; Ruihua Xu; Zumin Shi; Tingting Wang; Wenxiu Jian; Haijing Wang; Ruijie Xu; Lei Zhao; Youfa Wang; Wen Peng (Public Health Nutrition)
Abstract